Epistemologi Psikoanalisa: Menggali Kepribadian Sosial Dalam Perspektif Sigmund Freud - Khoirul Fatih, Moh. (MADINAH, 2019)
Since the Renaissance, science in the Western World developed rapidly, this is marked by the emergence of a variety of paradigms, methodologies, and concepts that color scientific studies, especially humanities studies such as psychology, anthropology, literature, history. The influence of Sigmund Freud's Psychoanalytic Theory in the study of modern psychology is quite dominant in coloring science in general that talks about humans, such as medicine, philosophy, religion, art, literature, anthropology, and politics. In the context of this human behavior controlled by his personality or personality, Freud explained in three terms namely, Id, Ego and Superego. Social personality in Freud's perspective is that sexual and aggressive impulse is innate which is part of human nature, serves to seek pleasure and satisfaction. The role of the social environment is blocking natural biological impulses as social control, while the main function of culture is to limit sexual life.